Financial inclusion in Morocco: The impact of financial development, financial innovation and economic growth - El Haddad, Salim; Idrissi, Abdelkader; Habachi, Mohamed (Edelweiss Applied Science and Technology, 2024)
The relationship between financial inclusion, social development, particularly poverty reduction, financial innovation and economic growth has been endorsed by a number of studies. Indeed, the development policies pursued by countries such as Morocco often define financial inclusion, growth, financial development, financial innovation, monetary policy and investment as fields of action for economic and social development. The aim of this study is to assess this choice by examining the short- and long-term relationship between financial inclusion, financial development, financial innovation, growth, inflation and the interest rate. Using the ARDL (AutoRegressive Distributed Lag) model and the Granger causality test, the results show the positive short- and long-term effect of financial development and financial innovation on financial inclusion, and the positive short- and negative long-term effect of economic growth on financial inclusion. The inflation and the interest rate that represents monetary policy influence financial inclusion in the short and long term positively and negatively respectively. In terms of causality, the granger test shows that economic growth has an effect on inclusion in only one direction and that financial inclusion has an effect on financial development in only one direction. On the other hand, innovation, inflation and the interest rate have a bidirectional relationship with financial inclusion.